Degradation of Paracetamol by Photolysis Using C-N-codoped TiO2 - Vanny Yulia Safitri; Adlis Santoni; Diana Vanda Wellia; Khoiriah Khoiriah; Safni Safni (Molekul, 2017)
Paracetamol is generally used as analgesic and antipyretic drugs. Contamination paracetamol in the environment can occur because of waste material disposal from production site and immediate disposal of household that cause water pollution. Paracetamol is degraded by photolysis method under irradiation 10 watt UV-light (λ=365 nm), visible-light (Philips LED 13 watt 1400 lux) and solar-light with and without addition C-N-codoped TiO2catalyst. The solution is analyzed by UV-Vis spectrophotometer at λ 200-400 nm. Optimum weight of C-N-codoped TiO2 catalyst obtained is 20 mg under UV-light photolysis. Paracetamol 4 mg/L is degraded 45.48% after 120 minutes under UV-light irradiation without catalyst, and increases to be 69.31% by using 20 mg catalyst. While degradation percentage of paracetamol is 16.96 % without catalyst, the percentage increases to be 34.29% after using 20 mg catalyst for 120 minutes photolysis under visible-light. Degradation of paracetamol by solar light achieves only 12.27% in absance of catalyst for 120 minutes irradiation, but it increases significantly until 70.39% in presence of 20 mg catalyst.